Does Actual Taxable Income Contain Valuable Information For Shareholders? Evidence From Finland - Laitinen, Erkki K.; Laitinen, Teija (Archives of Business Research, 2017)
There is much discussion about usefulness of book-tax differences in evaluating firm performance. This study contributes to this discussion assessing the information content of estimated and actual taxable income for Finnish corporate data from 2012-2013. The findings for year 2012 show that book income has higher explanation power of stock returns than other income concepts. However, estimated taxable income does not bring any incremental explanatory power to book income whereas actual taxable income contains more relative and also incremental information. The findings show that the explanation power of estimated taxable income in high earnings quality firms is comparable with that of book income but insignificant in low earnings quality firms. On the contrary, the explanation power of actual taxable income is lower in high earnings quality firms and higher in low earnings quality firms. For high earnings quality firms, neither of the taxable income concepts brings incremental information to book income. For low earnings quality firms, estimated taxable income does not bring any incremental information to book income whereas actual taxable income does. For these firms, actual taxable income brings significant incremental information also to estimated taxable income. For year 2013, anticipated significant tax rate reduction largely mitigated the relevant relationships between returns and income concepts.